2016
DOI: 10.1016/j.combustflame.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A slice of an aluminum particle: Examining grains, strain and reactivity

Abstract: Micron-scale aluminum (Al) particles are plagued by incomplete combustion that inhibits their reactivity. One approach to improving reactivity is to anneal Al particles to increase dilatational (volumetric) strain which has also been linked to increased combustion performance. While optimal annealing temperatures have been identified (roughly 300 °C), little is known about cooling rate effects on particle combustion performance. This study examines the effect of quenching after annealing Al microparticles to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Note that these numbers were in quantitative agreement with theoretical predictions based on the melt dispersion mechanism. 1,2 Similar results on increased reactivity were obtained in McCollum et al 5 In particular, they found pre-stressed (PS) Al powder annealed at or above 300 C showed the highest increase in reactivity.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Note that these numbers were in quantitative agreement with theoretical predictions based on the melt dispersion mechanism. 1,2 Similar results on increased reactivity were obtained in McCollum et al 5 In particular, they found pre-stressed (PS) Al powder annealed at or above 300 C showed the highest increase in reactivity.…”
Section: Introductionsupporting
confidence: 81%
“…Both micron and nanometer scale Al particles are examined and material preparation and characterization was accomplished using established protocols. 5 Impact ignition analyses were accomplished by designing a pressurized reaction cell coupled with a traditional drop weight impact tester. The pressurized reaction cell is equipped with sensors to monitor the transient pressure and light intensity within the closed cell upon sample impact.…”
Section: Introductionmentioning
confidence: 99%
“…The results in eqn (19) show residual compressive stress and strain in the core at annealing temperature are much smaller than in the unrelaxed state at room temperature. Now we can rewrite eqn (13)- (15) for new reference temperature T a ¼ 573 K at which there is no creep strain in the shell (s h ¼ 0) and stress and strain in the core are determined by eqn (19). These new equations are shown in eqn (20)- (22) and indeed, for 3 h c ¼ 0 and T ¼ T a we obtain s h ¼ 0 and eqn (19).…”
Section: Equations For Al Core-al 2 O 3 Shellmentioning
confidence: 89%
“…Measurements from this beamline that quantify dilatational strain in mAl powder have been reported previously. [14][15][16][17] In contrast to previous measurements on mAl powder, data on the nAl particles were taken with a 10Â 2m 12 keV monochromatic beam because the size from the white beam focus (around 1 m) was not sufficiently small to resolve the nAl particles. For the nAl particles, data were taken in 'powder diffraction pattern' mode and dilatational strain was derived from the shis in 2q values of the powder rings with respect to their 'unstrained' positions.…”
Section: Synchrotron Xrd Measurements Of Strainmentioning
confidence: 99%
“…This change in stress state is linked to changes in reactivity. [11][12][13][14] In order to quantify the stress state within pre-stressed (PS) Al particles, several studies measure dilatational strain within the core [11][12][13][14] (e.g., the shell is amorphous, and the strain cannot be directly measured via X-ray diffraction). The primary diagnostic to resolve dilatational strain in the Al particle core-shell structure is synchrotron X-ray diffraction (XRD) using the combined white and monochromatic microbeam approach at the Advanced Light Source (ALS) 15 Particles annealed to 573 K (300 C) and quenched at moderate rates (i.e., <100 K/min) led to a significant increase in dilatational strain, corresponding to a tensile stress in the Al core and compressive stress in the Al 2 O 3 shell.…”
Section: Introductionmentioning
confidence: 99%